Expresiones artísticas con física y matemática para todos - Vergara Mejía, Helen (2025)
This work arose from an activity carried out in a classroom for sixth- and seventh-grade students in 2014 at the Pestalozzi District Educational Institution in Barranquilla; the students plotted the color code for electrical resistors on a Cartesian plane. In 2017, I developed a diagnostic test to assess the students’ level of learning in relation to potentiation and rooting. Two activities were carried out: a theoretical calculation of the value of an electrical resistor, and a practical activity using a multimeter. I then created different figures representing the color code for electrical resistors, which were depicted on canvases and a 3D representation of the color code. The ludic part involved solving a sudoku; the students replaced the numbers in the sudoku with the color code for electrical resistors.